A Review on the Neuroanatomy of Bee Brain and Social Behavior - Nongkhlaw, Ridahunlang (Current Indian Science, 2024)
At present, there is a growing interest among researchers in studying the structure and function of the bee brain in relation to their cognitive behavior. The bee brain, despite its small size of approximately 1 million neurons, is known for its ability to facilitate effective communication and collaboration. Just like humans, the bee brain is also controlled by biogenic amines like dopamine, serotonin and tyramine, octopamine, and histamine. The honey bees communicate with each other by using a complex language called the “waggle dance”. Despite existing knowledge about the bee brain's neuroanatomy, there is still a need to understand which specific regions control cognition and social behavior in bees. This review aims to explore the different major parts of the bee brain and how each part contributes to modulating social behavior.
Keywords: Social behavior